Zaproszenie do publikacji w piątym numerze „Tematów i Kontekstów” pt. "Polska proza nowa i najnowsza" - Pasterska, Jolanta (Tematy i Konteksty, 2014)
This is to announce the content of the next issue of “Tematy i Konteksty”, which was given the title “The New and the Latest Polish Prose”.